Knowledge on the Health Effects of Welding Smoke, Use of PPE Among Electric-Arc Welders in Ilorin South, North Central Nigeria - ADEWOYE, Kayode Rasaq; AWOYEMI, Ademola Olugbenga; IBIRONGBE, Demilade Olusola; BABATUNDE, Oluwole Adeyemi; IBRAHIM, Tayo (Journal of Asian Scientific Research, 2013)
INTRODUCTION: Electric arc welding and oxy-fuel gas welding are the commonest welding technologies used in small scale industries in Nigeria. Electric arc welders are exposed to serious health hazards like exposure to welding smoke. Health effects of such exposure include metal fume fever, and increased risk of chronic diseases and cancers. Exposure to welding smoke can be minimized by use of PPE. The aim of the study is to determine the knowledge of welders on health implication of welding smoke and use of PPE.MATERIALS AND METHODS: This cross sectional study was carrried out among self-employed electric-arc welders, their journeymen and apprentices with at least six months working experience in Ilorin South Local Government Area. Simple randomn sampling technique was used in selecting the 285 respondents. Data was collected using pre-tested interviewer-administered semi-structured questionnaire, and analyzed using EPI-INFO version 3.5.1. P-value of less than or equal to 0.05 was considered statistically significant. RESULTS: A total of 285 respondents were interviewed. Close to two third of the respondents 185 (64.9%) had poor knowledge of the health effects of welding smoke. There was a statistically significant relationship between the knowledge on health effects of welding smoke and the use of face-mask during welding operation (p = 0.0000). Forty three point five percent of all the respondents that used Face-mask during welding operation, reported always use of Face-mask, 34.8% used Face-mask often while 21.7% used face-mask occasionally. Of the respondents that used Eye-goggles during welding operation, 51.3% always used Eye-goggles, 23.1% often used Eye-goggles while 23.6% used Eye-goggles occasionally.CONCLUSION: Knowledge of the respondents on the health effects of welding smoke is poor among the majority of the respondents and it has influence on the use of face-mask. There is need to have health education session for this category of workers.